IMPLEMENTASI “ISI PIRINGKU” STRATEGI PENCEGAHAN STUNTING LEWAT PEMBERDAYAAN KELUARGA DI DESA LAUT DENDANG - Hutahaean, Masta Melati; Lisbeth Febriani Br Sinaga; Krisdamayanti Zai; Ruth Olyvia Pakpahan; Naomi Cynthia Rizki Gultom; Enjel Usmaria Sitorus (Fakultas Pertanian, 2023)
Introduction: Stunting is a national problem that must be handled in a comprehensive and multi-sectoral manner. Collaboration and synergy of all elements of the nation is urgently needed to create a stunting-free generation for Golden Indonesia 2045. The problems faced by partners include the high incidence of under-fives experiencing malnutrition problems, namely 151 under-fives (31.5%) due to lack of fulfillment intake of nutritional content in each food consumed so that it is necessary to carry out an intervention that can empower mothers and families and improve children's nutritional status. Purpose: The purpose of this activity is to increase the knowledge and attitudes of the community, especially mothers who have babies and toddlers and the ability of mothers who have babies and toddlers in preparing main meals and snacks that are healthy, halal and delicious. Method: The research method used is a quantitative method with a one group pretest posttest design without including a comparison group (control), but the first observation (pretest) has been carried out. Results: Based on the counseling t-test analysis of mothers' knowledge and attitudes, it is known that the p value is 0.001, which indicates that there are differences in knowledge and attitudes before and after the counseling is carried out. Conclusion: After participating in this outreach activity, it was discovered that there was an increase in the knowledge and attitudes of mothers who have babies and toddlers regarding balanced nutrition and mothers were able to apply ways to prepare healthy, halal and delicious food.